A Real-World Experience With the Supera Interwoven Nitinol Stent in Femoropopliteal Arteries: Midterm Patency Results and Failure Analysis. (June 2016) - Myint, Michael; Schouten, Olaf; Bourke, Victor; Thomas, Shannon D.; Lennox, Andrew F.; Varcoe, Ramon L.
Purpose: To evaluate the safety and midterm patency of the Supera interwoven nitinol stent in a real-world population and determine deployment and patient-related factors that may predispose to loss of patency.Methods: A retrospective analysis was conducted of 111 consecutive limbs from 97 patients (mean age 75.3 years; 68 men) with severe atherosclerotic disease of the superficial femoral and popliteal arteries that were treated with Supera stents between June 2012 and October 2014. Half the patients had claudication (56%); the remainder had rest pain (19%) and tissue loss (26%). Forty-eight (43%) lesions were chronic total occlusions, and more than half were classified as TransAtlantic Inter-Society Consensus C (22%) or D (30%).Results: All 146 Supera stents (1.32 stents per limb) were deployed successfully, extending over a mean length of 175.5±130.5 mm to treat lesions averaging 151.5±127.1 mm long. At 30 days, Kaplan-Meier estimated freedom from death, target lesion revascularization, and amputation was 97.3%. Primary patency and freedom from clinically driven target lesion revascularization rates were 87.1% and 95.0% at 6 months, respectively, and 78.9% and 87.6% at 12 months, respectively. Four distinct mechanisms for failure were identified in the 13 limbs in which patency was lost; stent intussusception (n=4), compromised inflow or outflow (n=2), gross oversizing (n=1), and neoplastic thrombophilia (n=1); the cause of 5 occlusions could not be identified.Conclusion: In this heterogeneous group that included long and complex atheromatous femoropopliteal lesions, the Supera stent achieved excellent clinical and patency results at 1 year. Further improvement may be achieved through careful patient selection and the avoidance of deployment pitfalls.